Noninvasive Optical Imaging and In Vivo Cell Tracking of Indocyanine Green Labeled Human Stem Cells Transplanted at Superficial or In-Depth Tissue of SCID Mice - Vikram Sabapathy; Jyothsna Mentam; Paul Mazhuvanchary Jacob; Sanjay Kumar (Stem Cells International)
Stem cell based therapies hold great promise for the treatment of human diseases; however results from several recent clinical studies have not shown a level of efficacy required for their use as a first-line therapy, because more often in these studies fate of the transplanted cells is unknown. Thus monitoring the real-time fate of in vivo transplanted cells is essential to validate the full potential of stem cells based therapy. Recent studies have shown how real-time in vivo molecular imaging has helped in identifying hurdles towards clinical translation and designing potential strategies that may contribute to successful transplantation of stem cells and improved outcomes. At present, there are no cost effective and efficient labeling techniques for tracking the cells under in vivo conditions. Indocyanine green (ICG) is a safer, economical, and superior labelling technique for in vivo optical imaging. ICG is a FDA-approved agent and decades of usage have clearly established the effectiveness of ICG for human clinical applications. In this study, we have optimized the ICG labelling conditions that is optimal for noninvasive optical imaging and demonstrated that ICG labelled cells can be successfully used for in vivo cell tracking applications in SCID mice injury models.